N-myc downstream-regulated gene 2 (NDRG2) promoter methylation and expression in pituitary adenoma - Paulina Vaitkiene; Indre Valiulyte; Brigita Glebauskiene; Rasa Liutkeviciene (BMC, 2017)
Abstract Background Pituitary adenoma (PA) is a benign primary tumor that arises from the pituitary gland and is associated with ophthalmological, neurological and endocrinological abnormalities. However, causes that increase tumor progressing recurrence and invasiveness are still undetermined. Several studies have shown N-myc downstream regulated gene 2 (NDRG2) as a tumor suppressor gene, but the role of NDRG2 gene in pituitary adenoma pathogenesis has not been elucidated. The aim of our research has been to examine NDRG2 mRNA expression in PA and to determine the associations between the NDRG2 gene epigenetic changes and the development of recurrence or invasiveness of PA and patient clinical data. Methods The MS-PCR was used for NDRG2 promoter methylation analysis and gene mRNA expression levels were evaluated by qRT-PCR in 68 non-functioning and 73 functioning adenomas. Invasiveness was evaluated using magnetic resonance imaging with Hardy's modified criteria. Statistical analysis was performed to find correlations between NDRG2 gene mRNA expression, promoter methylation and patient clinical characteristics and PA activity. Results The NDRG2 mRNA expression was significantly lower in the case of acromegaly (GH and IGF-1 hypersecretion) than in other diagnoses of PAs (p < 0.05). Also, the NDRG2 expression was significantly higher in prolactinoma (PRL hypersecretion) than in in other diagnoses of PAs (p < 0.05). The promoter of NDRG2 was methylated in 22.69% (12/58 functioning and 15/61 non-functioning) of patients with PA. However, the NDRG2 gene mRNA expression was not significantly related to its methylation status. Clinical factors, such as: age, gender, relapse and diagnoses of Cushing syndrome were of no significance for NDRG2 promoter methylation and mRNA expression levels, as well as secreting or non-secreting PAs and the invasiveness of PAs. Conclusion The different NDRG2 promoter methylation and expression levels in PA samples showed tumor heterogeneity and indicates a potential role of this gene in pituitary adenoma pathogenesis, but the corresponding details require intensive research.